PENGARUH KEPEMIMPINAN TERHADAP KINERJA PARAMEDIS DAN DAMPAKNYA PADA MUTU PELAYANAN DI RSUD PASURUAN - Panjaitan, Hotman (Jurnal Riset Ekonomi dan Bisnis, 2010)
Generally health care services puts the quality of service as a primary goal, it is because the quality of service is a major supports the organization's performance expectations of stakeholders of the company. This study analyses the Effects of leadership and paramedics performance towards quality of service.The population of this study were employees, paramedics, and patients at Pasuruan Regional General Hospital. From the test results of the model in the research, with using random sampling technique, structural equation model analysis, and helps from AMOS 18 software, onto 150 samples, can be explained that the relationship between leadership and nursing performance towards service quality in RSUD Pasuruan, East Java.The results showed a significant positive influence among the leadership towards service quality, a significant positive effect between leadership towards nursing performance, and a significant positive influence between nursing performance towards service quality.Keywords: leadership, performance, service quality